2020
DOI: 10.1101/2020.05.31.125633
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

TMEM106BandCPOXare genetic determinants of cerebrospinal fluid Alzheimer’s disease biomarker levels

Abstract: Background: Neurofilament light (NF-L), chitinase-3-like protein 1 (YKL-40), and neurogranin (Ng) are utilized as biomarkers for Alzheimer's disease (AD), to monitor axonal damage, astroglial activation, and synaptic degeneration, respectively. Here we performed genome-wide association study (GWAS) analyses using all three biomarkers as outcome. Methods: DNA and cerebrospinal fluid (CSF) samples originated from the European Medical Information Framework AD Multimodal Biomarker Discovery (EMIF-AD MBD) study.… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

5
0

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 44 publications
0
12
0
Order By: Relevance
“…TMEM106B affects neuronal loss 46 and has been convincingly associated with risk for at least two forms of dementias, i.e. fronto-temporal dementia 46 and AD 13,41,47 . CHI3L1 encodes the YKL-40 protein and we and others have previously demonstrated that common and possibly rare variants at this locus represent cis pQTLs of CSF YKL-40.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…TMEM106B affects neuronal loss 46 and has been convincingly associated with risk for at least two forms of dementias, i.e. fronto-temporal dementia 46 and AD 13,41,47 . CHI3L1 encodes the YKL-40 protein and we and others have previously demonstrated that common and possibly rare variants at this locus represent cis pQTLs of CSF YKL-40.…”
Section: Discussionmentioning
confidence: 99%
“…Please see Hong et al for a detailed description of the GWAS methods, QC criteria and processing pipeline. 13 For X-chromosome specific methods, see supplementary methods.…”
Section: Methodsmentioning
confidence: 99%
“…Educational attainment was assessed as education years until highest degree [72]; this information was available for 994 participants. Lastly, we controlled for genetic ancestry by using the first four principal components from a principal component analysis on genome-wide SNP genotyping data [73] generated in the same individuals.…”
Section: Methodsmentioning
confidence: 99%
“…shared custom content (Illumina, Inc.) using procedures outlined in Hong et al (29). To compute cis mQTLs (defined as within ±1 Mb of the CpG site) in this dataset we used the matrix eQTL software (30), which performed an additive linear model with sex, genetic PC 1 to 5, and genotyping batch as covariates.…”
Section: Identification Of Mqtls In Buccal Samples From An Independent Datasetmentioning
confidence: 99%
“…DNAm data were derived from buccal-swab samples and generated and processed using the same procedures described above. Genome-wide SNP genotyping data were generated from the same samples using the "Global Screening Array" (GSA) with shared custom content (Illumina, Inc.) using procedures outlined in Hong et al (29). To compute cis mQTLs (defined as within ±1 Mb of the CpG site) in this dataset we used the matrix eQTL software (30), which performed an additive linear model with sex, genetic PC 1 to 5, and genotyping batch as covariates.…”
Section: Identification Of Mqtls In Buccal Samples From An Independent Datasetmentioning
confidence: 99%